Statistical characteristics of narrow-banded ELF emissions observed on board ISIS satellite - Saito, Hiroaki; Yoshino, Takeo; Sato, Natsuo (1986)
P(論文) Occurrence distributions of narrow-banded ELF emissions over the southern polar region have been studied statistically from ISIS-1 and -2 VLF data which were received at Syowa Station (L=6.1) in Antarctica. It is found that emissions occurred mostly during the evening to the pre-midnight of 17-24 MLT and in the region of 65°-75° invariant latitude associated with V-shaped VLF hiss emissions. The emissions occurred during disturbed geomagnetic activities and the occurrence region shifted to lower latitude in association with geomagnetic activities. It is also found that the emissions have their occurrence maximum during the austral winter season from April to July. The emission frequencies are strongly depending on the height of the satellite position. departmental bulletin paper